2011
DOI: 10.1017/s002193201100071x
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and Obesity Prevalence Among Oecd Countries

Abstract: Using recent pooled data from the World Health Organization Global Infobase and the World Factbook compiled by the Central Intelligence Agency of the United States, this study assesses the relation between income inequality and obesity prevalence among 31 OECD countries through a series of bivariate and multivariate linear regressions. The United States and Mexico well lead OECD countries in both obesity prevalence and income inequality. A sensitivity analysis suggests that the inclusion or exclusion of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
(54 reference statements)
0
35
1
1
Order By: Relevance
“…While income inequality was treated as a potential confounding variable in this study, and was not the specific focus of any hypothesis, there has been sufficient research looking at income inequality as a putative cause of health inequality that the results are worthy of consideration here [26, 27, 31, 35, 36]. After controlling for national income, household income, and other individual level factors, national income inequality was not significantly associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While income inequality was treated as a potential confounding variable in this study, and was not the specific focus of any hypothesis, there has been sufficient research looking at income inequality as a putative cause of health inequality that the results are worthy of consideration here [26, 27, 31, 35, 36]. After controlling for national income, household income, and other individual level factors, national income inequality was not significantly associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between national income and BMI exists, with the prevalence of obesity being greater in developed countries than less developed countries, and obesity rates increasing as per capita incomes increases [29, 30]. However, some previous studies showed no association of BMI and national income, but the majority of these studies were based only on high-income countries [31]. …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that there may be stronger social pressure against obesity in women compared with men, and the pressure is stronger among women at higher socioeconomic status than among women at low socioeconomic status [33,39]. Although enough research on attitudes toward body weight has been conducted on young women, available reports suggest that body image dissatisfaction and weight preoccupation remain high in aging women [40].…”
Section: Discussionmentioning
confidence: 99%
“…59 There are also methodological issues regarding confounding variables, particularly associations between measures of SES and ethnicity. However, in the most extensively studied, if not necessarily representative, country 60 (USA), the association between one measure of SES (education) and BMI has weakened over the period 1970-2000. 61 It may be that SES now plays a more minor role compared to the national level of affluence in the most developed countries.…”
Section: Genetic Variants Contributing To Common Obesity Are Expressementioning
confidence: 99%